Design and Fabrication of Small-Scale Potato Peeling Machine with Lye Method. Issue 1 (May 2021) - Sandra,; Damayanti, R; Prayogi, I Y; Basukesti, A S
Abstract: Peeling or removing the skin is one of the main post-harvest processes in fruits and vegetables. At present, most of the peeling of fruits and vegetables is done manually using sharp objects / knives. This method of peeling causes more fruit flesh to be wasted, especially fruits / vegetables with thin skins. Therefore, the design of a machine that can peel thin-skinned fruits / vegetables using the lye peeling method is needed. The purpose of this study was to design and fabrication a machine that can peel fruits and vegetables after the pre-treatment process of soaking in hot NaOH. The way this machine works is by spraying pressurized water on the fruit soaked in hot NaOH solution. In this study, the object was potatoes. Control of water pressure coming out of the nozzle is done using the pulse width modulation (PWM) method with a potentiometer. The treatments were carried out using three duty cycle values with the analogue input setting value on the microcontroller which resulted in three variations of water pressure coming out of the nozzle, namely: 60% (4.2038 Pa); 80% (5.6051 Pa); and 100% (7, 0065 Pa). Respectively for low, medium and high levels. Treatment concentrations of NaOH were 9%, 11% and 13%. The results obtained were the percentage of perfectly peeled skin close to 100% was obtained at 11% NaOH with a duty cycle value of 60% and 80%; and 13% NaOH with a duty cycle value of 80%. The calculation of the smallest percentage weight loss is 14.96% at 9% NaOH duty cycle 100% and the highest percentage weight loss is 35.89% at 13% NaOH 80% duty cycle.